(untitled) (Research, Society and Development, 2021)
The oral mucositis is an adverse event of radiotherapy and/or high toxicity chemotherapy. The Solidago chilensis (Arnica) has been used for its antiseptic, analgesic, healing and anti-inflammatory properties. Objective: The purpose of this study was to evaluate the uses of Arnica for oral mucositis prevention in patients submitted to radiotherapy for head and neck tumors treatment and/or high toxicity chemotherapy. Methodology: The determination of the cytotoxicity index of the aqueous extract was determined in vitro. The oral mucosa was evaluated in days 0, 10 and 14 of patients in the groups: treated with lasertherapy (L, n=18), treated with Arnica (A, n=24) and, treated with lasertherapy associated with Arnica (LA, n=4). It was considered significant p<0.05. Results: It was determined IC50=90,74 μg/mL of Arnica’s aqueous extract in SCC-4 cells. The development of oral mucositis was associated with the type of treatment for oral mucositis prevention: L, A, and LA (χ2 = 24,72, p<0.0001). The level of oral mucositis had significant interaction with the type of prevention treatment [F(2) = 9.545, p<0.0001] and, within 14 days [F(2) = 11.995, p<0.0001]. Conclusions: The results obtained suggest which the use of Solidago chilensis (Arnica) can be an important therapeutic option for treatment with low-level laser therapy for oral mucositis prevention in patients submitted of head and neck radiotherapy and/or high toxicity chemotherapy.